Epilepsia partialis continua after an anterior circulation ischaemic stroke. (12th May 2017) - Bentes, C.; Franco, A. C.; Peralta, A. R.; Viana, P.; Martins, H.; Morgado, C.; Casimiro, C.; Fonseca, C.; Geraldes, R.; Canhão, P.; Pinho e Melo, T.; Paiva, T.; et al.
Abstract : Background and purpose: Although cerebrovascular disorders are the main cause of epilepsia partialis continua (EPC) in adulthood, the frequency of EPC after stroke is unknown. The aim was to prospectively ascertain its frequency 1 year after an ischaemic stroke. Methods: This was a prospective study of consecutive acute anterior circulation ischaemic stroke patients, previously independent, with an admission National Institutes of Health Stroke Scale score ≥4, an acute ischaemic lesion on imaging and no previous epileptic seizures. During admission patients received standardized diagnostic and medical care and were submitted to a neurophysiological evaluation protocol. One year after stroke, patients were re‐evaluated by an epilepsy expert neurologist and performed a video‐electroencephalogram with electromyography co‐registration whenever myoclonus was observed during neurological examination for jerk‐locked back averaging analysis (JLBA). EPC was defined as continuously repeated fragments of epileptic seizures, with preserved consciousness, lasting at least 1 h, and representing locally restricted epileptic activity. Results: In all, 151 acute anterior circulation stroke patients were consecutively included and prospectively evaluated, but 23 died in the first year. One year after stroke, from 127 patients alive, 117 (92.1%) underwent clinical and neurophysiological evaluation. In two (1.7%) patients, EPC diagnosis was made both by clinical and electroencephalographic criteria, namely JLBA. Both patients had a history of remote symptomatic seizures and one of them acute symptomatic seizures and non‐convulsive status epilepticus criteria during the first 7 days after stroke. Conclusions: Despite its low frequency, the high stroke incidence makes post‐stroke EPC relevant. This study draws attention to this recognizable condition with therapeutic and eventually prognostic implications.